Agronomic, Chemical, and Antioxidant Characterization of Grain Amaranths Grown in a Mediterranean Environment. Issue 5 (10th August 2017) - Gresta, Fabio; Guerrini, Alessandra; Sacchetti, Gianni; Tacchini, Massimo; Sortino, Orazio; Ceravolo, Giuseppe; Onofri, Andrea
Abstract : The use of amaranth ( Amaranthus spp.) in the food and dietary supplements industry is increasing. The aim of this work is to promote the Mediterranean area as a production hot spot, by using multivariate statistical analyses on data obtained in two‐year trials and relating to morphological, productive, and qualitative traits and antioxidant activity of 20 accessions of five amaranth species ( A. caudatus L., A. cruentus L., A. hybridus L., A. hypochondriacus × hybridus L., A. hypochondriacus L.). Amaranthus cruentus accessions (Mexicane and New Mexico) were stable and highly productive (>2.7 t seeds ha −1 ), while Kinnaury Dhankar accession showed the highest protein percentage (17%). Amaranthus hypochondriacus (Orange Giant and Burgundy) possessed the highest oil percentage (always above 5.7%). A high amount in linoleic, cis‐ oleic, and palmitic acids, and an interesting saturated/unsaturated acids ratio ranging from 0.26 ( A. hybridus ) to 0.32 ( A. hypochondriacus ) were detected. The unsaponifiable fraction revealed the abundance of squalene in all species, while total tocopherol concentrations were lower than expected.